Geopolitical Risk and Global Banking - Friederike Niepmann; Leslie Sheng Shen (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
How do banks respond to geopolitical risk, and is this response distinct from other macroeconomic risks? Using U.S. supervisory data and new geopolitical risk indices, we show that banks reduce cross-border lending to countries with elevated geopolitical risk but continue lending to those markets through foreign affiliates—unlike their response to other macro risks. Furthermore, banks reduce domestic lending when geopolitical risk rises abroad, especially when they operate foreign affiliates. A simple banking model in which geopolitical shocks feature expropriation risk can explain these findings: Foreign funding through affiliates limits downside losses, making affiliate divestment less attractive and amplifying domestic spillovers.
Keywords: F34; F36; G21; 330; geopolitical risk; bank lending; credit risk; international spillovers